Gene-environment interactions in Autism Spectrum Disorder (ASD): excess copy number variants (CNVs) in genes regulating the effect of environmental exposure to toxicants - Xavier Santos, João (2017)
ASD is an heterogeneous neurodevelopmental disorder, with an estimated heritability of 50% and a complex genetic etiology. Recent studies also implicate exposure to environmental factors in this disorder. We thus hypothesize that ASD is the result of the interaction of a genetic susceptibility with exposure to environmental toxicants early in development. Here we tested whether affected individuals have an excess of CNVs targeting genes involved in control of toxicant effects, including detoxification or regulation of barrier permeability (blood-brain barrier, placenta and respiratory cilia).